EFL Students’ Perception of the Use of Group Work - Kurniatu Rohmah; Moh. Hasbullah Isnaini; Putu Dian Danayanti Degeng (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Group work is an essential part of the learning process, especially for students at school. Group work is one part of the learning method that helps teachers involve students and provides opportunities for students to learn cooperatively. This study aims to determine students' perceptions of the implementation of group work in English class. This study used an instrument in the form of a survey involving 125 participants consisting of five classes from class xi of SMAN 2 Malang. The author uses five variables as a reference to what problems often occur when grouping and the leak of students’ motivation when studying. The author uses a descriptive technique by describing what problems usually happen to analyze the data obtained. The findings from this study indicate that students working in groups can improve their responsibility and share their ideas, time, and task, resulting in an increased chance of completing tasks quickly and achieving better scores.